"We Were Born from Beauty": Dis/Inheriting Genealogies of Refugee and Queer Shame in Ocean Vuong's On Earth We're Briefly Gorgeous. (27th April 2022) - Cho, Jennifer
Abstract: I examine how Ocean Vuong's 2019 novel On Earth We're Briefly Gorgeous reconceives intergenerational shame produced through processes of refugee and queer becoming and identification in the United States. I posit that the affective condition of shame is both a result of and intrinsic to the social formation of queer and refugee identities. I also trace how these identities that at times can exclude the Other also intersect in On Earth as a way of revealing and critiquing the parallel forms of heteropatriarchal violence enacted upon the queer/refugee subject. Through Vuong's presentation of Little Dog's queer Vietnamese identity, I consider how Little Dog must reconcile himself to the loyalties that bind him to his matrilineal family and Vietnam and also to American idealizations of white masculinity and heterosexuality. These tensions are animated through the shame resulting from Little Dog's sexual encounters with his white American love interest, Trevor, and in Little Dog and his family's social "failures" to integrate into the United States and become model minorities. The sustained incompatibility between the matrilineal past of Vietnam (and the metonymic war the country signifies) and the American present belonging to the white fathers who fill the text also shows the limits of the dominant narratives that situate the United States in benevolent relation to the powerless refugees it saved and rehomed. Although I focus on the paralyzing effects of shame that attend experiences of racial and sexual difference, I explore how Vuong reimagines shame as a generative site that not only creates new intimacies and grammars across bodies that have been deemed socially abject but also conjures a Vietnam outside the familiar US war narrative of rescue.